Multimodal Approaches in Problem-Based, Project-Based, and Inquiry-Based Learning Models in Science Education: A Systematic Literature Review - Gunawan Gunawan; Ahmad Harjono; Kosim Kosim; Baiq Nabila Saufika Zainuri; Qothrunnada Qothrunnada (Indonesian Publication Center, 2025)
The shift in science education towards a constructivist approach requires integrating learning strategies that foster deep student engagement and understanding. This research systematically investigates the integration of multimodal approaches into Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Inquiry-Based Learning (IBL) models in science education, and evaluates their effectiveness on student learning outcomes. Employing a Systematic Literature Review (SLR) based on the PRISMA protocol, this study covers peer-reviewed sources from various international databases over the last 15 years. Findings consistently indicate that multimodal integration through simulations, virtual laboratories, multiple representations, videos, and other digital tools significantly improves conceptual understanding, critical thinking skills, creativity, and positive motivation and attitudes towards science. While each model offers specific advantages (PBL excels in problem analysis, PjBL in artifact creation, and IBL in scientific exploration), successful implementation depends heavily on the teacher's role, student readiness, and contextual support. This review recommends well-planned multimodal learning designs that align with learning objectives and the specific model's characteristics.